THE EFFECT OF PRICE EARNING RATIO, DIVIDEND POLICY AND FUNDING DECISIONS ON COMPANY VALUE IN THE PROPERTY AND REAL ESTATE SECTOR LISTED ON THE IDX - Widya Hartanti; Rico Nur Ilham; Nurlela; Chairil Akhyar (PT. Radja Intercontinental Publishing, 2025)
The purpose of this study is to determine the effect of price earning ratio, dividend policy, and funding decisions on company value in the property and real estate sector listed on the Indonesia Stock Exchange. This study uses a quantitative research type. The population is 93 companies, after purposive sampling technique, 10 companies were obtained with an observation year range from 2019 - 2023, so that there are 50 observation data. The method used in this study is panel data regression analysis. As dependent variables in this study, price earning ratio, dividend policy, funding decisions and company value as independent variables. The results of this study are that partially the price earning ratio and funding decisions have a positive and significant effect on company value, dividend policy has a positive but not significant effect on company value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX).